Strategi Peningkatan Kualitas Pelayanan Satgas PPKS Universitas Airlangga Melalui Implementasi Kebijakan - Ramasari, Amidita; Artika Sari, Tiara; Insofia, Fairuz Irsa (Jurnal Administrasi Publik dan Bisnis, 2025)
This study examines strategies for improving service quality of the Task Force for Prevention and Handling of Violence in Higher Education (Satgas PPKPT) through policy implementation at Airlangga University. Following the transition from Ministry of Education Regulation No. 30/2021 to Regulation No. 55/2024, this research analyzes how these policy changes impact service delivery. Using a qualitative descriptive approach, data was collected through interviews with Airlangga University's PPKPT Task Force team and analysis of relevant policy documents. Results indicate that policy implementation serves as an effective strategy for enhancing service quality through the development of Standard Operating Procedures (SOPs). Improvements were observed across five service quality dimensions: tangibility (provision of dedicated spaces), responsiveness (rapid response to reports), assurance (victim security guarantees), reliability (systematic handling procedures), and empathy (victim-centered services). The research confirms that integrated policy implementation contributes significantly to service quality by creating a safe academic environment, suggesting that similar approaches could benefit other higher education institutions implementing violence prevention programs. This study adds to the limited literature on how policy changes can be leveraged to enhance institutional responses to violence in academic settings.